2004
DOI: 10.1242/jcs.00941
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for structural and functional diversity among SDS-resistant SNARE complexes in neuroendocrine cells

Abstract: The core complex, formed by the SNARE proteins synaptobrevin 2, syntaxin 1 and SNAP-25, is an important component of the synaptic fusion machinery and shows remarkable in vitro stability, as exemplified by its SDS-resistance. In western blots, antibodies against one of these SNARE proteins reveal the existence of not only an SDS-resistant ternary complex but also as many as five bands between 60 and >200 kDa. Structural conformation as well as possible functions of these various complexes remained elusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…The responses observed during successive stimulations up to the 7 th one resulted quantitatively undistinguishable from those evoked by the first one (data not shown) as evidenced qualitatively in Figure 2D showing that no significant long-term effects occurred. In agreement with previous reports, [49][50][51][52][53] this survey of SDS on exocytosis confirmed that 250-350 μM corresponded to an adequate concentration range for our purpose in this study. Yet, to ensure the absence of any non-obvious long-term effects, only the spikes delivered during the first 10 s range after the first stimulation were treated quantitatively.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The responses observed during successive stimulations up to the 7 th one resulted quantitatively undistinguishable from those evoked by the first one (data not shown) as evidenced qualitatively in Figure 2D showing that no significant long-term effects occurred. In agreement with previous reports, [49][50][51][52][53] this survey of SDS on exocytosis confirmed that 250-350 μM corresponded to an adequate concentration range for our purpose in this study. Yet, to ensure the absence of any non-obvious long-term effects, only the spikes delivered during the first 10 s range after the first stimulation were treated quantitatively.…”
Section: Resultssupporting
confidence: 93%
“…42,43 Conversely, at the low concentrations used in this work SDS has been shown to have no effect on the SNAREs machineries that lead to initial fusion pores formation. 51,52 Hence, eliciting exocytosis by SDS at these low concentrations should not tamper at all with the formation of calcium-induced SNAREs complexes that initiates the critical process leading to the opening of the initial exocytotic fusion pores. Finally, it is important to note that exposing a cell to a brief pulse of low SDS concentrations cannot at all modify its vesicles internal structure nor their catecholamine content since this should require at least several minutes.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that high molecular weight (HMW) bands are not detected in samples that have been boiled prior to electrophoresis. However, in Giardia, when the samples were boiled, we found some peculiarities that had not been described in other eukaryotes (59). First, some of the putative gSNAREs (gQa1-4; gR1-3) presented almost the same bands obtained in unboiled samples, suggesting that the majority of HMW bands are not heat-sensitive (supplemental Fig.…”
Section: Western Blot Assays Of Giardia Putative Snares Revealed Slowmentioning
confidence: 49%
“…The four helices form a coiled-coil structure that in most cases is SDS-resistant at temperatures of ϳ80°C but not at boiling temperature (59). SDS-resistant SNARE complexes often exist in various forms with different electrophoretic motilities that give rise to multiple anti-SNARE-immunoreactive bands on Western blots (59).…”
Section: Western Blot Assays Of Giardia Putative Snares Revealed Slowmentioning
confidence: 99%
See 1 more Smart Citation